Empowering Local Wisdom: The Role of Tembang Bocah Banyumasan in Promoting Sustainable Development Goals in Banyumas, Indonesia - Emah Winangsit; Sunarto; Syahrul Syah Sinaga; Udi Utomo; Fajry Sub'haan Syah Sinaga; Chamil Arkhasa Nikko Mazlan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
Traditional cultural expressions offer robust, community-based pathways for advancing sustainable development; however, their concrete contributions to the Sustainable Development Goals (SDGs) are frequently overlooked in local policy and research. This study examines how Tembang Bocah Banyumasan supports SDG-related initiatives in Banyumas, Indonesia, with a particular focus on economic growth, health and well-being, education, and environmental awareness. Utilizing a qualitative phenomenological approach, data were gathered through in-depth interviews with musicologists, cultural activists, and community members involved in the production and promotion of this tradition. The findings were analyzed thematically through a sustainable development lens, linking cultural heritage and local wisdom to social transformation. Results indicate that Tembang Bocah Banyumasan not only solidifies cultural identity but also serves as an accessible platform for transmitting values, fostering children’s creativity, and encouraging civic participation. Furthermore, these cultural functions generate broader sustainability benefits by enhancing informal learning, reinforcing healthy social behaviors, stimulating creative economy opportunities, and promoting environmental stewardship. This study concludes that Tembang Bocah Banyumasan provides an authentic mechanism for localizing SDG initiatives while sustaining regional heritage and community resilience. Its novelty lies in the explicit mapping of a specific musical tradition to the SDGs, demonstrating how localized practices serve as grounded catalysts for sustainable development.